?A SENSOR FOR MONITORING WATER UPTAKE BY A SIMULATED PLANT ROOT - Ahmed, M; Mayet, Y; McCarthy, T T (Biological Sciences - PJSIR, 1999)
An optoelectronic device for measuring very slow rates of flow through a simulated plant root was designed, constructed and tested in the laboratory of Agricultural Engineering Department, University of Newcastle upon Tyne, England, during the period from 1985through 1987. 'Transducers' were used to monitor the advance rate of meniscus through a capillary glass tube. The transducers consisted of a small piece of plastic (Tufnol), a 6 mm filament bulb and a phototransistor unit.The time recordedby each transducer was printed out in a microprinter.The optoelectronic device reported in this paper can be used in the monitoring of soil water extraction by a physically simulated plant root which would ultimately allow plant water stress to be used directly in the control of irrigation.